2021
DOI: 10.1038/s41598-021-03898-1
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of patients with diabetes mellitus in The Philippine CORONA Study

Abstract: Patients diagnosed with diabetes mellitus (DM) who are infected with severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) belong to the most vulnerable patient subgroups. Emerging data has shown increased risks of severe infections, increased in ICU admissions, longer durations of admission, and increased mortality among coronavirus disease 2019 (COVID-19) patients with diabetes. We performed a subgroup analysis comparing the outcomes of patients diagnosed with DM (n = 2191) versus patients without DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…14 The lesser incidence of stroke among COVID-19 positive healthcare workers may be due to healthy-worker effect bias, i.e., health care workers or employed people, in general, have better health-seeking behavior or annual mandatory health examinations compared to the unemployed or elderly. 18 Similarly, the mortality and hazard rates among COVID-19 stroke patients were higher compared to those with COVID-19 alone. 9,10,19 Compared to western data, COVID-19 stroke patients in our study were 2.17 times more likely and with 3.45 times more likely to die due to several etiologies at a particular time (42.2% vs. 19.4%).…”
Section: Discussionmentioning
confidence: 94%
“…14 The lesser incidence of stroke among COVID-19 positive healthcare workers may be due to healthy-worker effect bias, i.e., health care workers or employed people, in general, have better health-seeking behavior or annual mandatory health examinations compared to the unemployed or elderly. 18 Similarly, the mortality and hazard rates among COVID-19 stroke patients were higher compared to those with COVID-19 alone. 9,10,19 Compared to western data, COVID-19 stroke patients in our study were 2.17 times more likely and with 3.45 times more likely to die due to several etiologies at a particular time (42.2% vs. 19.4%).…”
Section: Discussionmentioning
confidence: 94%
“…Also, the possibility of a spurious result concerning the association of AP use and negative COVID-19 outcomes cannot be ruled out. AP show a heterogeneous but significant positive association with metabolic complications ( Pillinger et al, 2020 ; Zhang et al, 2017 ), and the presence of metabolic comorbidities such as diabetes or metabolic syndrome among COVID-19 patients significantly increased the risk of mortality, respiratory failure, duration of ventilator dependence, severe/critical COVID-19, ICU admission, and length of hospital stay ( Denson et al, 2021 ; Espiritu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, different studies have shown that people with T2DM have higher risk of COVID-19 mortality compared with non-diabetic individuals [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Nevertheless, Al-Salameh et al, reported that COVID-19-related death in patients with T2DM was lower than in general population, but the rate of intensive care unit (ICU) admission was increased [ 20 ].…”
Section: T2dm As a Risk Factor For The Development And Prognosis Of C...mentioning
confidence: 99%